Analisis Pengaruh Motivasi terhadap Hasil Belajar Matematika - Tangdilintin, Lidia Aprilia; Suradi, Suradi; Danial, Danial (Jurnal Pendidikan Matematika : Judika Education, 2026)
This study aims to analyze and synthesize various previous research results regarding the influence of learning motivation on mathematics learning outcomes. The method used is library research with a qualitative descriptive approach to relevant scientific sources in the last ten years. The results show that learning motivation has a positive and significant effect on mathematics learning outcomes at various levels of education. The higher the students' motivation, the better the learning outcomes achieved, which indicates that learning motivation plays an important role in promoting academic success. Although the level of influence of motivation varies between studies due to differences in context, education levels, and other internal and external factors, motivation remains one of the key factors that support the effectiveness of the learning process.   Keywords: Learning Outcomes, Motivation, Literature Study.